Lung transplantation after allogeneic stem cell transplantation: a pan-European experience. Issue 2 (15th February 2018) - Greer, Mark; Berastegui, Cristina; Jaksch, Peter; Benden, Christian; Aubert, John; Roux, Antoine; Lhuillier, Elodie; Hirschi, Sandrine; Reynaud-Gaubert, Martine; Philit, François; Claustre, Johanna; LePalud, Pierre; et al.
Late-onset noninfectious pulmonary complications (LONIPCs) affect 6% of allogeneic stem cell transplantation (SCT) recipients within 5 years, conferring subsequent 5-year survival of 50%. Lung transplantation is rarely performed in this setting due to concomitant extrapulmonary morbidity, excessive immunosuppression and concerns about recurring malignancy being considered contraindications. This study assesses survival in highly selected patients undergoing lung transplantation for LONIPCs after SCT. SCT patients undergoing lung transplantation at 20 European centres between 1996 and 2014 were included. Clinical data pre- and post-lung transplantation were reviewed. Propensity score-matched controls were generated from the Eurotransplant and Scandiatransplant registries. Kaplan–Meier survival analysis and Cox proportional hazard regression models evaluating predictors of graft loss were performed. Graft survival at 1, 3 and 5 years of 84%, 72% and 67%, respectively, among the 105 SCT patients proved comparable to controls (p=0.75). Sepsis accounted for 15 out of 37 deaths (41%), with prior mechanical ventilation (HR 6.9, 95% CI 1.0–46.7; p<0.001) the leading risk factor. No SCT-specific risk factors were identified. Recurring malignancy occurred in four patients (4%). Lung transplantation <2 years post-SCT increased all-cause 1-year mortality (HR 7.5, 95% CI 2.3–23.8; p=0.001). Lung transplantation outcomes following SCT were comparable to other end-stage diseases. Lung transplantation should be considered feasible in selected candidates. No SCT-specific factors influencing outcome were identified within this carefully selected patient cohort. Lung transplantation is feasible in selected stem cell transplant recipients http://ow.ly/z4vn30h6gao